RESPON MASYARAKAT TERHADAP AKTIVITAS PASAR KAGET PAHLAWAN KERJA DI KELURAHAN MAHARATU KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Nur Aska Desy; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The presence of a Pasar Kaget in Pekanbaru is currently very fast growing. Counting thousands of merchants who sell in various Pasar Kaget in the City. One of them is like what happened in Maharatu Village District of Marpoyan Damai . When the Pasar Kaget is open, then people's access will be very difficult to pass by the community. This study aims to determine the Pasar Kaget activities work heroes and analyze the impact of Pasar Kaget Activities at the surrounding community. This study uses descriptive quantitative methods. The population in this study amounted to 54 people. Sampling is done by using saturated sampling techniques with a total sample of 54 respondents. Data collection uses the method of observation, quesionary and documentation. Based on the results of the study it can be concluded that the type of merchandise sold in the Pasar Kaget is 61.5% in the form of staples. Parking arrangements in the Pasar Kaget  that 85.2% of work heroes are not good. The presence of a Pasar Kaget at Jalan Pahlawan Kerja 79.6% has a positive response on the social interaction of the surrounding community. The existence of the Pasar Kaget amidst 79.6% community settlements providing easy access to needs and distance. Keywords:Response, Pasar Kaget